Solve:(2x+3)(x-4)=(2x-3)(x+3)
Answers
Answered by
7
(2x + 3) × (x - 4) = (2x - 3) × (x + 3)
Multiply the brackets
☛ 2x² - 8x + 3x - 12 = 2x² + 6x - 3x - 9
Cancel the equal terms of 2x² on LHS and 2x² on RHS
☛ -8x + 3x - 12 = 6x - 3x - 9
Collect the like terms together
☛ -5x - 12 = 3x - 9
Move the terms
☛ -5x - 3x = -9 + 12
Calculate
☛ -8x = 3
Dividing both thw sides by -8, we get
☛ x = -3/8
∴ The value of x is
Multiply the brackets
☛ 2x² - 8x + 3x - 12 = 2x² + 6x - 3x - 9
Cancel the equal terms of 2x² on LHS and 2x² on RHS
☛ -8x + 3x - 12 = 6x - 3x - 9
Collect the like terms together
☛ -5x - 12 = 3x - 9
Move the terms
☛ -5x - 3x = -9 + 12
Calculate
☛ -8x = 3
Dividing both thw sides by -8, we get
☛ x = -3/8
∴ The value of x is
Answered by
10
Solve :
We'll start with opening up these given brackets
Since the term
=》
Take all the variables on the left side, and the constants on the right side and solve :
=》
Do the necessary operations on the numbers :
=》
Take (-8) on the right side :
=》
Similar questions